2016
DOI: 10.1111/cmi.12566
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicansinfection leads to barrier breakdown and a MAPK/NF-κB mediated stress response in the intestinal epithelial cell line C2BBe1

Abstract: Intestinal epithelial cells (IEC) form a tight barrier to the gut lumen. Paracellular permeability of the intestinal barrier is regulated by tight junction proteins and can be modulated by microorganisms and other stimuli. The polymorphic fungus Candida albicans, a frequent commensal of the human mucosa, has the capacity of traversing this barrier and establishing systemic disease within the host. Infection of polarized C2BBe1 IEC with wild-type C. albicans led to a transient increase of transepithelial electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 69 publications
5
38
2
Order By: Relevance
“…As previously reported, the expression of TJ proteins can be regulated by multiple signaling pathways, including mitogen‐activated protein kinases (MAPKs), mammalian targets of rapamycin (mTOR), and myosin light chain kinase (MLCK). Figure A showed that arctigenin (3 µM) did not alter ERK, JNK, and P38 activation after stimulation with TNF‐α in Caco‐2 and HT‐29 cells, but inhibited the phosphorylation of mTOR and the downstream adaptor protein RPS6.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As previously reported, the expression of TJ proteins can be regulated by multiple signaling pathways, including mitogen‐activated protein kinases (MAPKs), mammalian targets of rapamycin (mTOR), and myosin light chain kinase (MLCK). Figure A showed that arctigenin (3 µM) did not alter ERK, JNK, and P38 activation after stimulation with TNF‐α in Caco‐2 and HT‐29 cells, but inhibited the phosphorylation of mTOR and the downstream adaptor protein RPS6.…”
Section: Resultsmentioning
confidence: 95%
“…To shed light on the action mechanism of arctigenin, this work investigated its effects on the activation of three important pathways (MAPKs, mTOR, and MLCK) which are relevant in the expression of TJ proteins. [29][30][31] The results showed that arctigenin did not affect the activation of ERK, JNK and P38 induced by TNF-α in colon epithelial cells, but inhibited the phosphorylation of mTOR, the expression of MLCK and phosphorylation of MLC. When arctigenin was used in combination with rapamycin (an inhibitor of mTOR) or fasudil (an inhibitor of MLCK), rapamycin rather than fasudil augmented the promotion effect of arctigenin on the expression of occludin and ZO-1 in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since C. albicans has the capacity of traversing the intestinal epithelial barrier and can also alter its permeability (27), and CEACAM1 expression also influences vascular (28, 29) and colonic (30) permeability, we next tested whether CEACAM1 knockdown affects the epithelial barrier function. All cell lines were grown on Transwell filters and tested for two permeability parameters: i.e., the ability to prevent the permeation of fluorescein isothiocyanate (FITC)-dextran and transepithelial electrical resistance (TEER).…”
Section: Resultsmentioning
confidence: 99%
“…176 However, less is known about the direct regulation of the secretion of AMPs by C. albicans and the gut mycobiota. Interestingly, in this context, microarraybased transcriptomic analyses of intestinal epithelial cells interacting with C. albicans did not report overexpression of AMPs-related genes following infection, 177 whereas a strong expression of AMPs (especially DEFB4) was observed in oral cells challenged with the fungus. 177,178 Once more, these observations corroborate the view that molecular and cellular features characterizing C. albicans interactions depend on the type of host cell.…”
Section: Interaction Of C Albicans With the Gut Mucosal Barriermentioning
confidence: 96%